Chemical, Physiological and Molecular Responses of Host Plants to Lepidopteran Egg-Laying - Bertea, Cinzia Margherita; Casacci, Luca Pietro; Bonelli, Simona; Zampollo, Arianna; Barbero, Francesca (Frontiers in Plant Science, 2020)
Plant-lepidopteran interactions involve complex processes encompassing molecules and regulators to counteract defense responses they develop against each other. Lepidoptera identify plants for oviposition and exploit them as larval food sources to complete their development. In turn, plants adopt different strategies to overcome and limit herbivorous damages. The insect egg deposition on leaves can already induce a number of defense responses in several plant species. This minireview deals with the main features involved in the interaction between plants and lepidopteran egg-laying, focusing on responses from both insect and plant side. We discuss different aspects of direct and indirect plant responses triggered by lepidopteran oviposition. In particular, we focus our attention on the mechanisms underlying egg-induced plant defenses that can i) directly damage the eggs such as localized hypersensitive response (HR)-like necrosis, neoplasm formation, production of ovicidal compounds and ii) indirect defenses, such as production of oviposition-induced plant volatiles (OIPVs) used to attract natural enemies (parasitoids) able to kill the eggs or hatching larvae. We provide an overview of chemical, physiological and molecular egg-mediated plant responses induced by both specialist and generalist lepidopteran species, also dealing with effectors, elicitors and chemical signals involved in the process. Egg-associated microorganisms are also discussed, although little is known about this third partner participating in plant-lepidopteran interactions.